Preferensi Mahasiswa Terhadap Daya Tarik Mie Gacoan dalam Perspektif Masyarakat - Novia Herman Devi; Wulan Ayu Ningsih; Syamsul Hidayat (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to analyze students' preferences toward the appeal of Megacoan from a societal perspective. A descriptive approach using a survey method was employed to collect data from university students across various institutions. The findings reveal that factors such as product innovation, marketing strategies, service quality, and brand image play a significant role in shaping students' preferences for Megacoan. Moreover, the influence of societal opinion is a crucial element that enhances the appeal of Megacoan among students. This study provides valuable insights for business practitioners to understand the preferences of the younger generation and to design more effective and relevant marketing strategies.